Teclado chibcha: un software lingüístico para los sistemas de escritura de las lenguas bribri y cabécar. - Flores Solórzano, Sofía (2012)
The project Teclado Chibcha was designed to overcome the technical difficulties that face the indigenous people from Costa Rica, and in general the people interested in the study of their native languages, to write in digital media. The application allows stacking the diacritics used by the practical alphabets of the bribri and cabécar languages; all this thanks to the open font Charis SIL and a keyboard layout to facilitate the introduction of these characters in the operating system Windows. The result is a tool of easy installation that solves a technical problem with deep cultural and educational implications.